2020
DOI: 10.1177/1177180120954441
|View full text |Cite
|
Sign up to set email alerts
|

“The work of a leader is to carry the bones of the people”: exploring female-led articulation of Indigenous knowledge in an urban setting

Abstract: Although the activism and historic contributions of Indigenous female leaders to urban Indigenous community development across Turtle Island are recognized, there remains a dearth in the literature regarding the specific mechanisms that enabled Indigenous women to successfully articulate cultural knowledge and inform their management styles by traditional ways. The article explores some of the contributions of female leadership to the governance and program design of a large, culture-based urban Indigenous non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…While most intersectional scholarship attends to the ‘unique experiences of oppression and privilege’ (Fylling and Melboe, 2019: 90) produced through an individual’s location within power dynamics, scholars recognise that persons who occupy several categories of marginal identity do not necessarily experience additive oppression known as a ‘double handicap’ (Brooks and Deegan, 1981) or ‘double jeopardy’ (Rousso and Wehmeyer, 2001). There is evidence multiple subjectivities are the source of both oppression and agency, depending on the context (Maracle et al., 2020). For example, in a study of Norwegian Sami men with disabilities, Fylling and Melboe (2019) find that intersections of Indigeneity with conditions like hearing impairment and ADHD precipitate both structural oppression and opportunities for agency and freedom from judgement through connection with traditional livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…While most intersectional scholarship attends to the ‘unique experiences of oppression and privilege’ (Fylling and Melboe, 2019: 90) produced through an individual’s location within power dynamics, scholars recognise that persons who occupy several categories of marginal identity do not necessarily experience additive oppression known as a ‘double handicap’ (Brooks and Deegan, 1981) or ‘double jeopardy’ (Rousso and Wehmeyer, 2001). There is evidence multiple subjectivities are the source of both oppression and agency, depending on the context (Maracle et al., 2020). For example, in a study of Norwegian Sami men with disabilities, Fylling and Melboe (2019) find that intersections of Indigeneity with conditions like hearing impairment and ADHD precipitate both structural oppression and opportunities for agency and freedom from judgement through connection with traditional livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…Many Indigenous communities are matrilineal, meaning that people are seen as descending from their matriarchal lines, and women are central to health care decision making and passing culture down through generations ( Cesario, 2001 ). During the COVID-19 pandemic, Indigenous women's articulation of Indigenous knowledge through social media contributed to creating a community of service that respected distinct expressions of cultural and gender identity ( Maracle et al, 2020 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…While our relational ethics could be perceived as prolonging the research project, our collective experiences have shown that sharing our tears, laughter, rage, stories, and teachings immensely deepened and strengthened our ability to effectively collaborate on this project and to think more critically while fostering a wholesome self-esteem. We highly encourage collaborative research that values, respects, and enacts relational ethics upheld in Indigenous women's leadership and mentorship approaches (McGuire-Adams T, Gaudet JC, Ward J: The emotional labour of reconciliation: indigenous women creating kind spaces through the complexities and challenges of reconciliation in the academy, forthcoming), [20][21][22].…”
Section: Research Team and Framework For Conducting The Researchmentioning
confidence: 99%